The Role of ICT and Human Capital Development in Pursuing a Demographic Dividend and Improving Economic Welfare in Indonesia - Nurarifin; Sedwivia Ridena (Pusbindiklatren Bappenas, 2020)
This article aims to provide evidence that Information and Communication Technology (ICT) and human development play an important role in pursuing a demographic dividend and accelerating economic welfare in Indonesia by exploiting provincial data from 2012 to 2017. The empirical evidence implemented in this research is Two-Stage Least Squares and dynamic system Generalized Method of Moments (GMM) techniques. The results show that a 1%-point rise in ICT development growth potentially leads to an approximately 0.24%-point increase in economic welfare growth, whereas an in life expectancy may decrease GDP per capita. The analysis also finds that a 1%-point increase in the ratio of the participation rate will promote a nearly 0.16%-point rise in per capita output. Meanwhile, a 1%-point increase in the share of the working-age population will generate roughly 0.19%-point rise in per capita income. A recent paper suggests that policymakers have to promote more supportive ICT and human development policies to pursue a demographic dividend since even though they have a positive impact on per capita income, the magnitude remains relatively low.